Characteristics Associated with Successful Residency Match in General Surgery - Reagan A. Collins, BA; Kaitlyn Nimmer, BA; Salma A. Sheriff, BS; Tania K. Arora, MD; Anai N. Kothari, MD, MS; Carrie Cunningham, MD, MPH; Callisia N. Clarke, MD, MS (Annals of Surgery Open)
Objective:. To evaluate characteristics of matched and unmatched general surgery residency (GSR) applicants. Background:. Given the recent change of the United States Medical Licensing Exam Step 1 grading to pass/fail, understanding the factors that influence GSR match success is integral to identifying potential interventions to improve match rates for diverse medical students. Methods:. Retrospective review of GSR National Residency Matching Program (NRMP) applicant and Accreditation Council for Graduate Medical Education (ACGME) active resident data between 2011 and 2022. Data included application characteristics for United States (“US”) and “independent” applicants, factors cited by program directors in the interview and ranking process, paths pursued if applicants went unmatched, and racial/ethnic representation. Results:. A total of 9149 US and 3985 independent applicants applied to GSR between 2011 and 2021. Matched versus unmatched applicants had higher step 1 scores (US: 236 vs 218, P = 0.005; independent: 237 vs 228, P = 0.001), higher step 2 scores (US: 248 vs 232, P = 0.006; independent: 245 vs 234, P < 0.001), more likely to belong to alpha omega alpha (US: 17.1% vs 1.6%, P = 0.002) or to attend a top 40 National Institutes of Health-funded school (US: 31.0% vs 19.4%, P = 0.002) compared to unmatched applicants. Program directors heavily factored step 1 and step 2 scores, letters of recommendation, interactions with faculty and trainees, and interpersonal skills when interviewing and ranking applicants. The proportion of active general surgery residents versus applicants was lower for Asians (12.3% vs 20.9%, P < 0.001), Black/African American (5.0% vs 8.8%, P < 0.001), Hispanic/Latino (5.0% vs 9.4%, P = 0.001), and underrepresented in medicine students (10.3% vs 19.1%, P < 0.001). Conclusions:. In the pass/fail step 1 era, factors including step 2 score and other subjective metrics may be more heavily weighted in the GSR match process.